1984
DOI: 10.1017/s1742758400008626
|View full text |Cite
|
Sign up to set email alerts
|

1-Octen-3-ol. A potent olfactory stimulant and attractant for tsetse isolated from cattle odours

Abstract: Recording of electroantennographic (EAG) responses from tsetse, Glossina pallidipes and G. morsitans morsitans (Diptera: Glossinidae) has been used to detect olfactory stimulants in volatiles from cattle. The most potent stimulant in cattle odours collected on Porapak resin has been identified as 1-octen-3-ol by gas chromatographic retention data and mass spectrometry. The rate of production of l-octen-3-ol by a normal ox was estimated to be 0.043 mghr" 1 , and the natural material was shown to be predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
185
1
7

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(199 citation statements)
references
References 24 publications
6
185
1
7
Order By: Relevance
“…1-octen-3-ol, the most significant chemostimulant for tsetse in L. camara, is a previously described attractant for these flies in cattle odour (Hall et al, 1984) and is included in almost all odour baits for a range of tsetse species (Dransfield and Brightwell, 1992). We have quantified (by GC-EAD) the olfactory threshold of tsetse to be in the range of 0.1 ppt for this product, equivalent to detection threshold of male moths for their sex pheromones (Kaissling and Priesner, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…1-octen-3-ol, the most significant chemostimulant for tsetse in L. camara, is a previously described attractant for these flies in cattle odour (Hall et al, 1984) and is included in almost all odour baits for a range of tsetse species (Dransfield and Brightwell, 1992). We have quantified (by GC-EAD) the olfactory threshold of tsetse to be in the range of 0.1 ppt for this product, equivalent to detection threshold of male moths for their sex pheromones (Kaissling and Priesner, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of a series of kairomones for savannah tsetse from preferred hosts (Hall et al 1984;Owaga et al 1988) facilitated the development of baited traps and targets (the latter impregnated with insecticides) effective in large-scale suppression of these species (Vale et al 1988;Brightwell et al 1991). Several synthetic and natural repellents, including a constituent of bovid odours, 2-methoxyphenol, have been evaluated but were found not to be sufficiently effective in protecting cattle in the field (Torr et al 1996).…”
Section: Prospects For Push-pull In Controlling Livestock Pests and Dmentioning
confidence: 99%
“…Studies have, however, shown that 1-octen-3-ol and acetone can increase net movement of C. impunctatus in a Y-tube olfactometer (Basin et al, 2000). Both acetone and 1-octen-3-o1 have been found to be attractive to the tsetsefly (Hall et al, 1984;Vale, 1980). Vale & Hall (1985b) increased flies catches of Glossina morsitans moritans and G. pallidipes by up to three times by releasing 1-octen-3-o1 at 0.5-50 mg/h or acetone at 5-500 mg/h near traps.…”
Section: Chemical Vapours Tests 1-octen-3-olmentioning
confidence: 99%